1979
DOI: 10.1093/bja/51.11.1079
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Effects of the Sitting Position in Neurosurgery

Abstract: The cardiorespiratory effects of raising patients from the supine to the sitting position for neurosurgery were investigated. The change caused marked decreases in cardiac index, stroke volume, PaO2 and Qs/Qt, with a significant increase in (PAO2-PaO2) and total peripheral resistance. It is concluded that patients who maintain normotension in the sitting position do not necessarily have an adequate circulatory status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Previous studies on the respiratory effect of sitting position during neurosurgery reported the decrease in lung oxygenation and increase in dead-space ventilation, which are partly consistent with the results of the present study [ 8 , 9 ]. In the present study, the dead-space ventilation was increased in the normocapnia group but the oxygenation index was not changed in the sitting position.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies on the respiratory effect of sitting position during neurosurgery reported the decrease in lung oxygenation and increase in dead-space ventilation, which are partly consistent with the results of the present study [ 8 , 9 ]. In the present study, the dead-space ventilation was increased in the normocapnia group but the oxygenation index was not changed in the sitting position.…”
Section: Discussionsupporting
confidence: 93%
“…However, hypoventilation of the lungs may result in atelectasis and increase in intrapulmonary shunt, which leads to hypoxemia and lung injury [ 6 , 7 ]. In previous studies on respiratory effect of the sitting position during neurosurgery, sitting position was associated with decreased arterial oxygen tension (PaO 2 ) and increased dead-space ventilation (Vd/Vt) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of an intraoperative, semi-seated position on the gas exchange are also studied in neurosurgical patients [ 66 ]. The small amount of available data revealed an improvement of oxygenation in these patients.…”
Section: Backrest Elevation Positionmentioning
confidence: 99%
“…The resulting postural reduction in stroke volume (SV) and cardiac output (CO) impacts the circulation (Dalrymple et al, 1979; Porter et al, 1999; Buhre et al, 2000; Truijen et al, 2012). In healthy awake humans, baroreceptor reflex-mediated sympathetic activation with an increase in heart rate (HR) and vascular tone maintains mean arterial pressure (MAP), but induction of anesthesia with propofol attenuates this adaptive response.…”
Section: Introductionmentioning
confidence: 99%
“…While several studies focused on the perioperative hemodynamic challenge of the beach-chair position (Dalrymple et al, 1979; Porter et al, 1999; Buhre et al, 2000; Jeong et al, 2012; Moerman et al, 2012), no attention has been paid to the position of the patient during induction of anesthesia. It remains unsettled whether induction of anesthesia in the reclining vs. sitting beach-chair position secures cerebrovascular hemodynamics.…”
Section: Introductionmentioning
confidence: 99%